Engineering Towards Catalytic Use of Fungal Class-II Peroxidases for Dye-Decolorizing and Conversion of Lignin Model Compounds - Lundell, Taina; Bentley, Elodie; Hilden, Kristiina; Rytioja, Johanna; Kuuskeri, Jaana; F. Ufot, Usenobong; Nousiainen, Paula; Hofrichter, Martin; Wahlsten, Matti; Doyle, Wendy; T. Smith, Andrew (Current Biotechnology, 2017)
Background: Manganese peroxidases (MnP) and lignin peroxidases (LiP) are haem-including fungal secreted class-II peroxidases, which are interesting oxidoreductases in protein engineering aimed at designing of biocatalysts for lignin and lignocellulose conversion, dye compound degradation, activation of aromatic compounds, and biofuel production. Objective. Recombinant short-type MnP (Pr-MnP3) of the white rot fungus Phlebia radiata, and its manganese- binding site (E40, E44, D186) directed variants were produced and characterized. To allow catalytic applications, enzymatic bleaching of Reactive Blue 5 and conversion of lignin-like compounds by engineered class- II peroxidases were explored. Method: Pr-MnP3 and its variants were expressed in Escherichia coli. The resultant body proteins were lysed, purified and refolded into haem-including enzymes in 6-7% protein recovery, and examined spectroscopically and kinetically. Results: Successful production of active enzymes was attained, with spectral characteristics of high-spin class-II peroxidases. Recombinant Pr-MnP3 demonstrated high affinity to Mn2+, which was noticeably affected by single (D186H/N) and double (E40H+E44H) mutations. Without addition of Mn2+, Pr- MnP3 was able to oxidize ABTS and decolorize Reactive Blue 5. Pc-LiPH8, its Trp-radical site variants, and engineered CiP-LiP demonstrated conversion of veratryl alcohol and dimeric non-phenolic lignin-model compounds (arylglycerol-β-aryl ethers) with production of veratraldehyde, which is evidence for cation radical formation with subsequent Cα-Cβ cleavage. Pc-LiPH8 and CiP variants were able to effectively oxidize and convert the phenolic dimer (guaiacylglycerol-β-guaiacyl ether). Conclusion: Our results demonstrate suitability of engineered MnP and LiP peroxidases for dyedecolorizing, and efficiency of LiP and its variants for activation and degradation of phenolic and nonphenolic lignin-like aryl ether-linked compounds.
Keywords: recombinant enzyme